Retrospective cohort study of predictors of loss to follow up among adolescents and young adults living with HIV on ART in Dar es Salaam, Tanzania, 2015–2019 - Magreth Thadei Mwakilasa; Maryam Amour; Suleiman Chombo; Joan Rugemalila; Emmanuel Balandya; Blandina T. Mmbaga; Lameck Machumi; Angelica Rugarabamu; Michael Johnson Mahande; David Sando; Bruno F. Sunguya (BMC Infectious Diseases)
Abstract Background In Tanzania, loss to follow-up (LTFU) among adolescents and young adults living with HIV (AYLHIV) presents a significant challenge. A retrospective cohort study analysing data found that approximately 42% of adolescents on antiretroviral therapy (ART) were LTFU between 2014 to 2016. This study examined the predictors of LTFU among AYLHIV in Dar es Salaam during their first year of ART treatment. Methods This retrospective cohort study utilized routine data collected in care and treatment centres among adolescents and young adults aged 10–24 years living with HIV in Dar es Salaam who were enrolled in HIV care from 2015–2019. The data were analysed using STATA 14. Descriptive statistics were summarized using frequencies and proportions. Kaplan–Meier method was used to determine failure probabilities within one year of ART initiation. The Fine and Gray test was conducted to report adjusted sub-hazard ratios (aSHRs) and cumulative incidence estimates for LTFU within one year of ART initiation, accounting for mortality as a competing risk. Results A total of 15,874 AYLHIVs enrolled in Care and Treatment Clinics between 2015 and 2019 were studied. The majority (10,913, 68.7%) were young adults, and 13,160 (84.4%) were female. The percentage of LTFUs within one year of ART initiation was 15%. The significant predictors of LTFU were age 20–24 years, having a CD4 cell count between 350 and 499, receiving care in healthcare facilities located in the Ubungo district and being enrolled in care between 2018 and 2019. Receiving care at private healthcare facilities, having a tuberculosis co-infection, and being classified as WHO Stage III were all associated with a reduced risk of LTFU in ART care. Conclusion This study found that adolescents and young people in Tanzania experience 15% rates of LTFU in ART care, within one year of ART initiation. Therefore, HIV service providers need to pay particular attention to the AYLHIV and factors that influence LTFU in ART care. The increasing incidence of LTFU necessitates the implementation of effective and friendly tracing interventions to identify AYLHIV patients who have become LTFU to re-engage them in care.